1995
DOI: 10.1074/jbc.270.48.28892
|View full text |Cite
|
Sign up to set email alerts
|

In HepG2 Cells, Translocation, Not Degradation, Determines the Fate of the de Novo Synthesized Apolipoprotein B

Abstract: Previous studies show that translocation and degradation of apolipoprotein B (apoB), two processes occurring on or within the endoplasmic reticulum, determine how much de novo synthesized apoB is secreted. We determined which of these processes regulates the intracellular fate of apoB by examining whether degradation determines how much apoB is translocated or if translocation determines how much apoB is degraded. 35 S]methionine-labeled proteins), its effect on apoB was specific. Pulsechase studies showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 39 publications
8
43
0
Order By: Relevance
“…OA does not affect the ability of ALLN to protect apoB in cells not treated with BFA; in fact, OA and ALLN have additive effects on apoB secretion (14). The results suggested, therefore, that (1) ALLN reduced apoB degradation in BFAtreated cells, possibly by inhibiting the initial degradation of partially translocated apoB (14,15) and (2) OA, by increasing apoB translocation across the ER membrane (see experiment below), exposed apoB to an ER luminal proteolytic process that was ALLN-resistant. The failure of OA to protect apoB in BFA-treated cells was not the result of failure to stimulate new triglyceride (11).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…OA does not affect the ability of ALLN to protect apoB in cells not treated with BFA; in fact, OA and ALLN have additive effects on apoB secretion (14). The results suggested, therefore, that (1) ALLN reduced apoB degradation in BFAtreated cells, possibly by inhibiting the initial degradation of partially translocated apoB (14,15) and (2) OA, by increasing apoB translocation across the ER membrane (see experiment below), exposed apoB to an ER luminal proteolytic process that was ALLN-resistant. The failure of OA to protect apoB in BFA-treated cells was not the result of failure to stimulate new triglyceride (11).…”
Section: Resultsmentioning
confidence: 95%
“…OA-induced translocation is probably the result of enhanced interaction between apoB and the microsomal triglyceride transfer protein (16). ALLN does not seem to facilitate the translocation of apoB across the ER membrane (14,15). Direct protection of apoB, either by inhibition of a neutral cystine protease or proteasome activity (17), is the likely mechanism underlying the effect of ALLN.…”
Section: Apobmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20]22,57 Evidence that the actual process of apoB translocation across the ER may be a crucial regulatory point in the production of lipoproteins has recently been suggested by Rusiñol and Vance. 22 They have shown that the supplementation of primary rat hepatocytes with phosphatidyl-monomethylethanolamine decreased the secretion of apoB.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin Digestion-Trypsin digestion of microsomes was done according to Bonnardel and Davis (16). Microsomes were suspended in 0.25 M sucrose and 10 mM HEPES, pH 7.4.…”
Section: Reagents-trypsinmentioning
confidence: 99%